The political economy of attention and electoral accountability - Patrick Balles; Ulrich Matter; Alois Stutzer (University of Basel, Center of Business and Economics (WWZ), 2024)
In this survey, we investigate the general mechanisms underlying the political economy of attention and review their empirical relevance, in particular for electoral accountability. The focus is on exogenous or stimulus-driven attention that political actors try to win or divert when pursuing their private interests. The corresponding evidence refers to representatives' reactions to general shifts in media attention and persuasive content as well as to short-term fluctuations in attention when exploiting anticipated attention shifts or attention shocks. In the context of digitization and the Internet, we consider the substitution effects between alternative media sources, the role of algorithmic content selection in informational segregation (or echo chambers), and the new opportunities of individual-level targeting strategies to steer attention.
Keywords: D72; D83; L82; L86; 330; accountability; attention; media; representative democracy; re-election